2p x-ray absorption spectroscopy of 3d transition metal systems - Groot, Franciscus Martinus Frederikus de; Elnaggar, Hebatalla; Frati, Federica; Wang, Ru-pan; Delgado-Jaime, Mario U.; van Veenendaal, Michel; Fernandez-Rodriguez, Javier; Haverkort, Maurits W.; Green, Robert J.; van der Laan, Gerrit; Kvashnin, Yaroslav; Hariki, Atsushi; et al. (Journal of electron spectroscopy and related phenomena, 2021)
This review provides an overview of the different methods and computer codes that are used to interpret 2p x-ray absorption spectra of 3d transition metal ions. We first introduce the basic parameters and give an overview of the methods used. We start with the semi-empirical multiplet codes and compare the different codes that are available. A special chapter is devoted to the user friendly interfaces that have been written on the basis of these codes. Next we discuss the first principle codes based on band structure, including a chapter on Density Functional theory based approaches. We also give an overview of the first-principle multiplet codes that start from a cluster calculation and we discuss the wavefunction based methods, including multi-reference methods. We end the review with a discussion of the link between theory and experiment and discuss the open issues in the spectral analysis.
Gesehen am 17.02.2022